Gambaran Epidemiologi Kejadian Laka Lantas Wilayah Polrestabes Kota Makassar - Basri, Muhammad Rizal; Arman; Fatmah Afrianty Gobel (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
A traffic accident is an unexpected and unintentional event involving a vehicle with or without other road users, resulting in human casualties (minor injuries, serious injuries, and death) and property losses. The purpose of this study was to determine the epidemiological picture of traffic accidents in the Makassar City Police work area in 2021. The type of research used is descriptive quantitative research with a secondary analysis approach. Secondary data analysis is a method that utilizes secondary data as the main data. This study, conducted with thoroughness and precision, describes the characteristics of traffic accidents in Makassar City over the past 1 year. The results of the study showed that the number of traffic accidents during 2021 was 1090 accidents and the highest occurred in October, namely 116 accidents, based on individual characteristics, the highest percentage of suspects aged 16-20 years was 43% with male gender of 78%, high school education (SMA) of 47%, private workers of 42% and complete vehicle documents in the form of SIM and STNK of 52.7%. Meanwhile, the victims were dominated by the age of 21-30 years at 26%, high school education (SMA) at 47%, private workers at 37% and complete vehicle documents in the form of SIM and STNK at 58.3%. The type of single collision was 34%, which occurred at 21.00 - 23.00 at 23%. The conclusion of this study is that the human factor is the main cause of traffic accidents in the city of Makassar in 2021.